Strategies using of Design of Experiments (DOE) techniques: In view of a review - Alashwal, Basma Yahya; Bala, Mohamed Saad; Gupta, Arun; Soubam, Triveni (School of Renewable Energy, Maejo University, 2021)
There Design of Experiment (DOE) has developed into a valuable collection technique for statistical and mathematical processes used in modelling and analysis of problems involving multiple variables influencing the desired response. Numerous researchers and engineers use this technique in a variety of fields, including botany, pharmaceuticals, biotechnology, and other engineering disciplines. This review article summarised key points from the Design of Experiments Using Response Surface Methodology (RSM). Design of experiments (DOE) has guidelines and procedures, but the literature does not recommend a specific method for finding and selecting the best possible design from a large number of possible designs